Shattering the Phallocentric Barriers: Examining Gender Jurisprudence in the Context of Women’s Reservation and Political Empowerment in India - Rajeev Kumar Singh; Anushka Trivedi (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2025)
The Women’s Reservation Act of 2023 represents a landmark legal effort to promote gender equality in India’s political system. Despite progress in education and employment, women’s political participation, especially among marginalized groups such as Dalits, tribal communities, and religious minorities, remains limited due to intersecting forms of discrimination. This study aims to analyze the impact of the Women’s Reservation Act on the political representation of marginalized women, examining how intersectionality shapes their experiences and the extent to which the law addresses structural barriers. The research employs a qualitative approach, including a thorough review of relevant literature, legal analysis, and case studies focusing on underprivileged women’s political participation. This method allows for an in-depth understanding of the Act’s implementation challenges and its effects on marginalized groups. The Women’s Reservation Act is a crucial step toward enhancing women’s political empowerment; however, its success in combating intersecting discrimination depends on addressing deeper social and institutional obstacles. The study highlights the need for targeted interventions and policy reforms to ensure that political inclusion under the Act genuinely benefits all women, particularly those from marginalized backgrounds, thus paving the way for a more inclusive and representative democracy.